Jamestown Souvenir, Exposition March Two-step - Kathleen Whitlock::::::::: (Sun Publishing Co.)
Piano score, 6 p. Cover title: Jamestown Exposition. March two step. Score c1907 by Kathleen Whitlock. Publishers advertisements on p.[2] and verso of last leaf.